2007
DOI: 10.1002/cncr.22998
|View full text |Cite
|
Sign up to set email alerts
|

Racial disparities in breast cancer outcome

Abstract: Since the 1970s, overall age-adjusted breast cancer mortality rates in the U.S.have been higher among African American (AA) women than among Caucasian American (CA) women. The racial disparity is not fully explainable based on socioeconomic factors. Suspected biologic factors underlying this trend may be interpreted by both epidemiologic and clinical perspectives. Descriptive epidemiologic studies suggest that breast cancer may be a mixture of at least 2 main diseases and/or causal pathways. The first breast c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 62 publications
2
15
0
Order By: Relevance
“…There is a controversy concerning when women should start getting mammograms; such tests are currently recommended for women between 45 and 50 years of age, depending on case and family history. This might turn out to be too late for some women, considering the fact that the highest incidence rate for ethnic minorities is age 50 and below and that those with early onset are likely to have more aggressive disease 26. Our data indicates that studies on genetic markers in early-onset breast cancer patients may encourage women to rethink when they should start getting mammograms or other types of screening procedures 27,28…”
Section: Cancer Surveillance Reportmentioning
confidence: 88%
“…There is a controversy concerning when women should start getting mammograms; such tests are currently recommended for women between 45 and 50 years of age, depending on case and family history. This might turn out to be too late for some women, considering the fact that the highest incidence rate for ethnic minorities is age 50 and below and that those with early onset are likely to have more aggressive disease 26. Our data indicates that studies on genetic markers in early-onset breast cancer patients may encourage women to rethink when they should start getting mammograms or other types of screening procedures 27,28…”
Section: Cancer Surveillance Reportmentioning
confidence: 88%
“…With earlier diagnosis and better treatments, survival has been improving in all groups of breast cancer patients. However, disparities still exist between AA and White women, with possible contributors including differences in socioeconomic status (SES), access to health care, especially screening and adjuvant therapy, and molecular and pathologic mechanisms (36). In a recent, large, population-based study using SEER Medicare data to examine racial differences in breast cancer survival, Silber et al (7) found that, after accounting for the effects of demographics, clinical presentation, and treatment modalities, there remained a 4.4% 5-year survival disparity, suggesting additional factors contribute to these disparities in survival (7).…”
Section: Introductionmentioning
confidence: 99%
“…[4] These comparable incidence rates underscore the importance of equal access to health care in closing the breast cancer disparity gap across racial lines and socioeconomic strata; however, elimination of disparity expands beyond the concept of health care access but implies identification of disease-specific risk for different sub-populations. [5,6] Published findings comparing the treatment outcome of DCIS between African-American and White-American are inconclusive. Studies that have adjusted for pathologic prognostic indicators, i.e.…”
Section: Introductionmentioning
confidence: 99%